EVALUATION OF PAWPAW LEAVES EXTRACT AS ANTI-CORROSION AGENT FOR ALUMINIUM IN HYDROCHLORIC ACID MEDIUM (Nigerian Journal of Technology, 2017)
Pawpaw leaves extract was examined as anti-corrosion agent for aluminium in hydrochloric acid medium. The extract and corrosion product were analyzed using Fourier transform infrared spectrophotometer (FTIR). Thermometric, gravimetric, potentiodynamic polarization and scanning electron microscopic methods were employed in the study. The inhibition efficiency was optimized using Response Surface Methodology (RSM) of Design Expert Software 9. Inhibitor concentration (0.2 g/l – 1.0 g/l), temperature (303 K – 333 K) and time (1hour - 5 hours) were the considered factors. It was revealed that stretched C-H and O-H functional groups were predominantly responsible for the corrosion inhibition process. The adsorption of the extract on the aluminium surface adhered to the mechanism of physical adsorption. A quadratic model adequately described the inhibition process. Optimum inhibition efficiency of 80.58% was obtained at inhibitor concentration of 0.961 g/l, temperature of 311.459 K and time of 3.932 hrs. The extract is a mixed-type inhibitor that can control both cathodic and anodic corrosion. http://dx.doi.org/10.4314/njt.v36i2.241